Human Input Measurement Methodology for Engineering Education - Gole, Surendra V.; Jolhe, Dhananjay A. (Journal of Engineering Education Transformations, 2007)
Human input measurement in service sector is really a different task. As the service organizations are concerned with the 'processes '(and not the 'products'), their performance are linked with the efficiencies of the input resources. A process, as in the case of engineering education, may have numerous inputs. The output, that is performance, of such a system is based on the complex interactions between these inputs. The present paper is an attempt toward the development of a methodology for the measurement of performance levels of the teacher's attributes as the input parameters. The paper, it is believed, can provide the important guidelines to all those who are concerned with evaluation&performance improvement of the engineering education.